Development Strategy of the Pharmacy Department at Nirmala Hospital based on SWOT Analysis - Suwanti, Ari; Yasin, Nanang Munif; Rahayu, Wiranti Sri (Journal of Health Economic and Policy Research (JHEPR), 2025)
Background: Medication management is a critical component of hospital operations, as inefficiencies can adversely affect hospitals medically, socially, and economically. This study aimed to assess the conformity of medication management practices and formulate development strategies at Nirmala Hospital's pharmacy department Methods: This descriptive analytical study used quantitative and qualitative methods, including observations, interviews, and questionnaires. The assessment was conducted based on standard medication management indicators. The Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis is used to formulate strategies based on the hospital’s internal and external aspects. Results: Medication selection, planning, and procurement processes generally met the standard indicators. However, the dead stock percentage was 1.54%, exceeding the acceptable limit. Two indicators did not meet standards: the average number of medications per inpatient prescription (6.82) and prescription conformity with the hospital formulary (85.71%). All distribution indicators met the required standards. Based on SWOT analysis, the pharmacy department is positioned in quadrant 1, indicating strong internal and external potential for service improvement. Conclusion: Under an aggressive growth policy, the recommended strategies include implementing a one-gate system, enhancing human resource capacity, and improving facilities to support pharmacy services. Keywords: Hospital’s Pharmacy Department, Medication Management, SWOT Analysis.